2008
DOI: 10.1063/1.2973588
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient ejection of H3+ from hydrocarbon molecules induced by ultrashort intense laser fields

Abstract: The ejection processes of hydrogen molecular ion H(3)(+) from 12 kinds of hydrocarbon molecular species, methanol, ethanol, 1-propanol, 2-propanol, acetone, acetaldehyde, methane, ethane, ethylene, allene, 1,3-butadiene, and cyclohexane, induced by intense laser fields (approximately 10(14) W/cm(2)) have been investigated by time-of-flight mass spectroscopy. The observation of the H(3)(+) production with the kinetic energy range of 3.5-5.0 eV from doubly ionized ethylene, allene, 1,3-butadiene, and cyclohexane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 14 publications
7
56
0
Order By: Relevance
“…From the number of events at Δt~500 fs in the high E kin region above 3.5 eV, the relative yields of the pathways (1), (2), (3), and (4) in our measurements are derived to be 1:1:0.07:3.6, respectively, showing that the three body explosion pathway (4) has the largest ion yield and the pathway (3) is a minor pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the number of events at Δt~500 fs in the high E kin region above 3.5 eV, the relative yields of the pathways (1), (2), (3), and (4) in our measurements are derived to be 1:1:0.07:3.6, respectively, showing that the three body explosion pathway (4) has the largest ion yield and the pathway (3) is a minor pathway.…”
Section: Resultsmentioning
confidence: 99%
“…For example, H 3 + formed through a bimolecular reaction, H 2 + +H 2 →H 3 + +H, can protonate a neutral molecule X by a subsequent bimolecular collision, H 3 + +X→HX + +H 2 , which may lead to further subsequent interstellar chemical reactions. It has also been shown that H 3 + can be emitted from hydrocarbon molecular dication prepared by electron impact ionization 2 , by extreme ultraviolet photoionization 3 , and by irradiation of intense femtosecond laser pulses [4][5][6] . The formation of H 3 + from allene [7][8][9] and the formation of HD 2 + from CD 3 OH 10 showed that migration of hydrogen atoms can proceed in the formation of H 3 + .…”
mentioning
confidence: 99%
“…PES for ground and excited states of the neutral, cation and dication states of acetylene were calculated on the CASSCF [10,10], [9,10] and [8,10] level of theory, respectively, using the program package MOL-PRO 35 with the 6-311þþG** basis set as well as the dipole moments and transition dipole moments. Two-dimensional PES were calculated along the symmetric and anti-symmetric stretching coordinate with a step size of 0.05 a.u..…”
Section: Methodsmentioning
confidence: 99%
“…Breaking of the hydrogen bonds is one of the most important dynamic reactions in the chemistry related to biology, combustion and catalysis, motivating considerable efforts to monitor and ultimately control the process. It has been studied in great detail, where efficient strong-field-induced proton ejection was reported [7][8][9][10][11][12][13][14] . Dynamic charge localization 11 and concerted fragmentation 12 scenarios were suggested to explain the origin of the high kinetic energies of the ejected protons.…”
mentioning
confidence: 99%
“…When hydrocarbon molecules are exposed to an intense laser field, a variety of dynamical processes originating from ultrafast motion of hydrogen atoms proceed such as ultrafast hydrogen migration and ejection of H 3 + , as has been shown in our recent studies on methanol [1], ethane [2][3][4], and other hydrocarbon molecules [2]. In the present study, in order to clarify how hydrogen atoms and/or protons migrate within an ethane molecule and to what extent the hydrogen atoms and protons exchange their positions among each other, we measured coincidence momentum imaging maps of fragment ions produced from ethane exposed to an intense laser field.…”
Section: Introductionmentioning
confidence: 99%